2019
DOI: 10.1080/1359432x.2019.1575364
|View full text |Cite
|
Sign up to set email alerts
|

Complementary variable- and person-centred approaches to the dimensionality of work engagement: a longitudinal investigation

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
92
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 42 publications
(125 citation statements)
references
References 108 publications
32
92
1
Order By: Relevance
“…Moreover, although these limited person-centered studies have generated insights into the nature and implications of the engagement construct, they also led to divergent conclusions regarding the importance of the various components of engagement. For instance, and contrary to theoretical predictions (Schaufeli & Bakker, 2004), Gillet et al (2019) showed that there might be benefits associated with the ability to maintain a healthy distance from work (i.e., low levels of absorption) among workers presenting a high level of work engagement (as measured with the UWES). In other words, there might be limits to the benefits associated with very high levels of work engagement.…”
contrasting
confidence: 69%
“…Moreover, although these limited person-centered studies have generated insights into the nature and implications of the engagement construct, they also led to divergent conclusions regarding the importance of the various components of engagement. For instance, and contrary to theoretical predictions (Schaufeli & Bakker, 2004), Gillet et al (2019) showed that there might be benefits associated with the ability to maintain a healthy distance from work (i.e., low levels of absorption) among workers presenting a high level of work engagement (as measured with the UWES). In other words, there might be limits to the benefits associated with very high levels of work engagement.…”
contrasting
confidence: 69%
“…In particular, the identification of such a large (49.0%) Balanced profile suggests that global levels of work fatigue remain adequate and aligned across dimensions for almost half of the participants. This finding is aligned with results from past studies of work engagement (Gillet et al, 2019a), well-being and psychological health (Morin et al, 2016b or need satisfaction (Gillet et al, 2019b), in which a similarly balanced profile was also found to characterized a large proportion of the sample.…”
Section: Employees' Work Fatigue Profilessupporting
confidence: 89%
“…In other words, it would seem that the lower level of work engagement would represent an essential condition for the negative relationship between workaholism and job performance to be significant. According to previous person-centered approaches to the study of the interplay between work engagement and workaholism by Gillet and colleagues [ 71 ], we could assume that disengaged workaholics could be at higher risk for underperforming at work. Moreover, the presence of work engagement as a moderator in the relationship between workaholism and job performance would explain the results obtained in previous studies revealing a nil relationship [ 11 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In corroboration, empirical support was found that work engagement can buffer against some of workaholism’s detrimental self-reported outcomes, such as work-family conflict, negative affect and emotional exhaustion [ 14 , 69 ], as well as on more objective measures, such as serum levels of the proinflammatory cytokine interleukin-17 (IL-17), a possible biomarker of stress [ 70 ]. The specific possible buffering effect of work engagement on workaholism’s poor job performance was addressed by Gillet, Caesens, Morin and Stinglhamber [ 71 ] in their person-centered approach. They found that job performance was worse for the disengaged workaholics than for the engaged workaholics.…”
Section: Introductionmentioning
confidence: 99%